1998
DOI: 10.2169/internalmedicine.37.32
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of Serum Aminotransferase as a Sign of Multiorgan-Disorders in Severely Emaciated Anorexia Nervosa.

Abstract: To clarify the clinical significance of elevation of serum aminotransferase levels in anorexia nervosa, we analyzed the relationships of serum aminotransferase levels to other serum biochemistry and physical conditions before and during refeeding therapy in 101 patients with anorexia nervosa. Before refeeding therapy, body mass index (BMI) was distributed from 9.9 to 16.4 kg/m2 (13.2 ± 1.3, mean ± SD), and 29 patients (28.7 % ) showed abnormally high aminotransferase levels. Among17 patients with a BMIof less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 17 publications
3
67
2
Order By: Relevance
“…In bivariate analyses, we found that BMI was inversely correlated with levels of ALT and GGT. Ozawa et al previously showed an inverse correlation between BMI and aminotransferase levels in severely malnourished hospitalized young women with AN (mean BMI 13.2 ± 1.3 kg/m 2 ) [22]. Therefore, the relationship between BMI and liver inflammation in AN may be present across a wide range of BMIs.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 94%
“…In bivariate analyses, we found that BMI was inversely correlated with levels of ALT and GGT. Ozawa et al previously showed an inverse correlation between BMI and aminotransferase levels in severely malnourished hospitalized young women with AN (mean BMI 13.2 ± 1.3 kg/m 2 ) [22]. Therefore, the relationship between BMI and liver inflammation in AN may be present across a wide range of BMIs.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 94%
“…In Japan, the frequency of hepatocellular damage on admission or prior to the effective therapy was reported to be 20% (2) or 29% (11). In the current study, we enrolled patients with eating disorders who had no previous nutritional treatment to exclude the possible hepatotoxic effect of nutritional support, and an elevation of ALT was observed in 52% (13/25), and all 13 patients were categorized as AN.…”
Section: Mild To Moderate Elevations Of Aminotransferases Are Occasiomentioning
confidence: 99%
“…With regard to liver function, available evidence suggests that abnormalities in serum liver enzymes occur to a various extent, [6][7][8][9][10][11][12][13][14][15][16][17][18][19] and some cases of acute liver failure have also been described, [20][21][22][23] while mild to moderate hypertransaminasemia has been observed during nutritional rehabilitation. 16 However, previous studies on serum liver enzymes in A-NERV still remain to a large extent contradictory and inconsistent because flawed by small sample size, inaccurate diagnosis, incomplete description of results and patient's characteristics, absence of control group, evaluation of only some of liver enzymes commonly considered in the clinical setting. In particular, a small body of evidence is so far available on serum cholinesterase, which is considered a marker of overall hepatocyte function and therefore likely to be influenced by nutritional status.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a small body of evidence is so far available on serum cholinesterase, which is considered a marker of overall hepatocyte function and therefore likely to be influenced by nutritional status. 16 Finally, to the best of our knowledge, no consistent data are available on serum liver enzymes in underweight patients with eating disorders not otherwise specified (EDNOS) who could also be at higher risk for malnutrition.…”
Section: Introductionmentioning
confidence: 99%